Model Pembinaan Karakter Dalam Menangani Perilaku Bullying Di Kalangan Santri (Studi Kasus Pondok Pesantren Puncak Darussalam) - Diny Chalishah, Naura; Aziz, Rahmat; Nur Wahyuni, Esa (JURNAL MANAJEMEN PENDIDIKAN, 2025)
A CHARACTER DEVELOPMENT MODEL FOR HANDLING BULLYING BEHAVIOR AMONG STUDENTS(Case Study of Puncak Darussalam Islamic Boarding School) Abstract. This study aims to describe the forms of bullying behavior, the factors causing it, and the handling model applied at Puncak Darussalam Islamic Boarding School, Pamekasan Regency. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, non-participatory observation, and documentation. The results of the study indicate that bullying behavior in the Islamic boarding school environment appears in various forms, namely verbal bullying in the form of teasing and insults, relational bullying such as ostracizing new students, and physical bullying which generally occurs in the form of spontaneous fights or mild aggressive actions. Factors causing the emergence of bullying in Islamic boarding schools include a strong seniority system, the normalization of a culture of violence as a form of discipline, and a low understanding of the values of manners and empathy among students. The crowded environment and intense daily activities also strengthen the potential for the emergence of domination between groups. Efforts to handle bullying in Islamic boarding schools are carried out through three main approaches. The preventive approach is carried out through character development, strengthening moral values, and the formation of a Character Building Team. The curative approach is implemented through mediation between the parties involved and religious counseling facilitated by the supervising ustaz. Meanwhile, the rehabilitative approach is aimed at restoring social relations so that victims and perpetrators can interact harmoniously again. The treatment model at Puncak Darussalam Islamic Boarding School emphasizes the principle of ta'dīb (ethical education) as a foundation for developing self-control, exemplary behavior, and moral habits. Research confirms that sustainable moral development, based on humanistic and spiritual values, is the key to realizing a safe, harmonious Islamic boarding school culture free from bullying.